Efficient secretory production of recombinant proteins in microalgae using an exogenous signal peptide - Le, Trang Thi; Tran, Quynh-Giao; Park, Su-Bin; Yoon, Hyang Ran; Choi, Dong-Yun; Cho, Dae-Hyun; Yun, Jin-Ho; Choi, Hong Il; Kim, Hee-Sik; Lee, Yong Jae (Frontiers in Microbiology, 2025)
Microalgae are promising platforms for recombinant protein production due to their scalability, rapid growth, safety, and sustainability. One strategy to reduce downstream processing costs is to secrete recombinant proteins directly into the culture medium, facilitated by signal peptides (SPs). However, the limited availability of effective SPs has hindered broader applications of this approach in microalgae. In this study, we identified a novel SP from a highly secreted protein of approximately 17 kDa in the culture medium of Chlorella sp. HS2. N-terminal sequencing via Edman degradation enabled identification of the corresponding gene, which encodes a hypothetical protein we designated MAPS (Most Abundant Protein in the Secretome). Bioinformatic analyses revealed a functional SP with features consistent with efficient secretory activity. To evaluate its utility, we generated transgenic Chlamydomonas reinhardtii strains expressing mCherry fused to this Chlorella sp. HS2-derived SP. Compared to two commonly used endogenous SPs from C. reinhardtii, the HS2-SP significantly enhanced mCherry secretion, achieving approximately two-fold higher levels in the culture medium. These findings highlight the potential of HS2-SP in improving recombinant protein secretion in C. reinhardtii, thereby supporting its application in algal biotechnology and industrial protein production.